Persepsi Siswa tentang Kompetensi Profesional Guru Bimbingan dan Konseling - Rosa, Silvia Silvia; Marjohan, Marjohan; Said, Azrul (Universitas Negeri Padang, 2014)
This research is classified as Â descriptive quantitative research. The research sample are 80 students SMPN7 of Padang. The findings this research: students' perceptions about the professional competence of teachers in terms of guidance and counseling master the concepts and practical assessment to understand the studentâ€™s conditions, needs, and problems are in either category.